Structural Transformation and Tax Efficiency - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2019)
Structural transformation has resulted in an increasing share of services in aggregate value-added in advanced and developing countries across the world. We analyze the impact of this shift into services on countries' efficiency in collecting the value-added tax (VAT). The analysis is based on two alternative measures of VAT efficiency: (1) the VAT C-efficiency, using a broad panel of 134 countries over the period 1970-2014; and (2) the VAT gap using a more granular, proprietary dataset that draws on the results of IMF's Revenue Administraion-Gap Analysis Program covering 24 countries over the period 2004-2016. We find that a higher share of services in aggregate value-added reduces the VAT efficiency, and that this adverse effect is mainly a result of a rise of non-tradable services, which in turn contributes to a narrowing of the VAT base.